Examining the Effectiveness of Integrative Training in Mindfulness Techniques and Self-Care on the Resilience of Parents with Children with Developmental Delay (A Single-Subject Study) - Etemadan , Maryam; Samani, Siamak; Amini Manesh, Sajjad; Bardideh, Mohammad Reza (KMAN Counseling & Psychology Nexus, 2025)
This study aimed to examine the effectiveness of an integrative protocol combining mindfulness techniques and self-care on the resilience of parents with children with developmental delay. This study employed a single-subject experimental design with an ABA framework. The statistical population included all parents of children aged 2 to 5 years with developmental delay who had undergone developmental screening by pediatric specialists in the city of Bushehr. The mothers completed the Ages and Stages Questionnaire (ASQ-3), and children diagnosed with developmental delays were referred to psychologists specializing in child rehabilitation in the second half of 2022 at two psychology clinics. From this population, five couples (10 parents) were selected through random sampling based on inclusion and exclusion criteria. The intervention was conducted over 16 sessions for the participating couples. The research instrument used was the Connor-Davidson Resilience Scale. Visual data analysis was performed at both intra-situational and inter-situational levels. The results indicated that the intervention involving the integrative protocol of mindfulness techniques and self-care had a significant positive impact on the resilience of parents with children with developmental delay. Based on the study's findings, the effectiveness of the integrative mindfulness and self-care protocol in enhancing the resilience of parents with children with developmental delay was confirmed. Therefore, this intervention can be considered a useful and practical therapeutic approach for these parents.